Navigating children's digital world safely: The role of positive parenting through digital literacy in densely population villages - Rosdiana, Aprilia Mega; Wahyuningtyas, Dessy Putri; Pramitha, Devi; A. Basid, Puspa Miladin Nuraida Safitri (Universitas Islam Negeri Ar-Raniry, 2025)
The development of the internet has provided easier access to information, entertainment, and communication. However, its use among the public has remained unstructured, particularly in supporting educational activities and positive parenting in the digital era. Various cyber risks have emerged, potentially affecting family well-being, especially in densely populated urban areas. This study aimed to describe the role and interaction between parents, families, communities, and local policies in enhancing digital literacy and family cyber resilience. This research employed a qualitative phenomenological approach with 16 respondents. Data were collected through focus group discussions and analyzed using Parson’s System Theory. The data analysis process followed the stages of open coding, axial coding, and selective coding. The validity of the data was tested through source triangulation, comparing FGD findings with in-depth interviews conducted with digital policy experts. The research showed that parents were concerned about their children's internet usage. Efforts to promote digital literacy were continuously carried out through collaboration among families, communities, government, and other stakeholders to strengthen cyber resilience in densely populated environments. The findings of this study could be utilized to support the development of effective empowerment and intervention programs to increase cyber resilience, enhance family welfare, and develop cyber resilience support systems in densely populated settlements.